The Role of Nanopartikel Green Tea in Enhancing Endothelial Cell Migration in HUVEC Culture exposed to EPC-Conditioned Media in Hyperglycemic Conditions - Yuly Peristiowati; Hariyono; Zauhani Kusnul; Reni Yuli Astutik; Nian Afrian Nuari (Universitas STRADA Indonesia, 2024)
Backgrounds: The role of endothelial progenitor cells (EPCs) in angiogenesis is impaired in diabetes mellitus. The present study was conducted to observe the effects of nanopartikel green tea on the ability of EPCs exposed to high levels of glucose to release NO and induce endothelial cell migration. Purpose: This study aims to describe the mechanism of the role of green tea nanoparticles in increasing migration of endothelial cells in HUVEC cultures exposed to EPC-CM. The function of EPCs was assessed by evaluating HUVEC migration after administration of EPC-Conditioned Media. HUVEC migration was assessed by the Boyden chamber assay method. Method: Green Tea Nano Particles treatment at doses of 30 nM and 50 nM significantly increased endothelial cell migration at high glucose exposure of 22 mM. At a dose of 50 nM, normal glucose exposure increased endothelial cell migration better than high glucose exposure. Administration of high levels of glucose resulted in a decrease in the ability of EPCs to induce HUVEC migration, decrease in NO of EPCs, and decrease in the factor affecting EPC migration, namely SDF-1α and CXCR4. Results: Administration of 50 μM of nanopartikel green tea could inhibit the decreased ability of EPCs to induce HUVEC migration, and this effect was associated with NO, SDF-1α and CXCR4 concentrations. Conclusions: Administration of nanopartikel green tea could maintain the ability of EPCs exposed to high levels of glucose to release NO and induce HUVEC migration through an increase in SDF-1α and CXCR4.